Efektivitas Model Pembelajaran Kontekstual untuk Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran Keterampilan Membaca - Husna, Nabila Miftahul; Muttaqin, Zainal; Zahra, Fatima El (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This study aims to examine the effectiveness of the contextual learning model in enhancing the learning motivation and reading skills of eighth-grade students at MTs Al Mursyidiyah Pamulang. The background of this research is based on the low interest and motivation of students in reading activities, particularly in the context of Arabic language learning. The method used is a quasi-experimental design with a pretest-posttest format involving two independent groups. The research sample consisted of two student groups: the experimental group, which applied the contextual learning model, and the control group, which used traditional teaching methods. The sampling was conducted using a census technique to obtain representative data. Data analysis included the Kolmogorov-Smirnov normality test and the Levene's test for homogeneity, both of which indicated that the data were normally distributed and homogeneous. The results of the Independent Sample T-Test revealed a significant difference between the two groups at a 0.05 significance level. These findings indicate that the contextual learning model has a positive and significant impact on improving students’ motivation and reading skills. The average post-test score of the experimental group was higher than that of the control group, reinforcing the effectiveness of the contextual approach. Therefore, the contextual learning model is effective and suitable to be used as an innovative strategy that can be implemented in the learning process, particularly in Arabic language instruction.